Computational analyses of the relation of theme and genre in the writing of aphra behn. Issue 1 (18th October 2019) - Mazel, Adam; Dumas, Catherine
ABSTRACT: This poster displays the results of preliminary computational analyses of the writing of Aphra Behn, a Restoration‐era woman of letters who wrote in a variety of genres. We analyze a selection of her diverse corpus via term frequency and topic modeling to consider how theme and genre relate in her writings: did Behn express similar themes in the many genres in which she wrote, or did she explore certain themes in certain genres, suggesting that her thematic interests determined the genres in which she wrote and vice versa? Analyzing the relationship between theme and genre in her writing offers insight into whether Behn adhered to the longstanding classical aesthetic concept of decorum : the belief, widespread when Behn wrote, that certain genres require certain themes and vice versa. Our preliminary analysis suggests both that she adhered to decorum and that computational text analysis is useful for studying theme and genre in individual authors.